Animated Canva Media Supports Storytelling Skills of Elementary Students: Media Animasi Canva Mendukung Keterampilan Bercerita Siswa Sekolah Dasar - Feren Pratiwi Pomalingo; Andi Paida; Ratnawati (Academia Open, 2025)
General Background: In the digital learning era, storytelling plays a critical role in developing students' speaking skills and creativity. However, traditional teaching methods often fail to foster students' confidence and engagement. Specific Background: Teachers at SD Inpres Hartaco Indah face challenges in guiding students with low storytelling confidence and limited access to engaging learning media. Knowledge Gap: While visual and animated media are known to enhance student engagement, there is limited empirical evidence on the use of Canva-based audiovisual media to improve storytelling skills in elementary students. Aims: This study aimed to develop and assess a Canva-based audiovisual animation learning media to improve storytelling skills among fourth-grade students. Results: The media was developed using the ADDIE model and validated by experts, receiving feasibility scores above 91%. Implementation in a real classroom showed very positive responses: ease of use (98.21%), visual appeal (96.55%), reliability (96.69%), and content quality (95.98%). Students demonstrated significant improvements in eight storytelling aspects, including expression, structure, and confidence. Novelty: This study presents a novel integration of Canva-based audiovisual design tailored to elementary learners' cognitive characteristics. Implications: The findings support Canva audiovisual media as a practical, effective tool for enhancing 21st-century storytelling skills and can be adapted across subjects and educational levels.Highlight : Canva's audio-visual animation-based media helps improve students' storytelling skills. Development uses a systematic and flexible ADDIE model. The media has proven to be highly feasible, practical, and effective based on validation and implementation results. Keywords :Learning Media, Canva, Audio Visual Animation, Storytelling Skills, ADDIE